The Impact of Organizational Justice on the Organizational Citizenship Behavior of Contract Workers in Indonesia: The Role of Exchange Quality and Multifocal Trust - Jati Waskito; Kussudyarsana Kussudyarsana; Imronudin Imronudin; Winda Linansya (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2023)
This study aims to examine the role of the double mediation of cognition-based trust and affect-based trust, along with the quality of the exchanges (perceived organizational support/POS and leader-member exchange/LMX), on the influence of organizational justice on organizational citizenship behavior (OCB). The survey involved 182 contract lecturers from the five top Muhammadiyah universities in Indonesia. Using structural equation models, this study has succeeded in demonstrating that the quality of the individual exchanges between supervisors and subordinates (LMX and affective-based trust) successfully mediate the sources of justice from the supervisors (interactional and informational justice). The quality of the individual exchanges with organizations (cognitive-based trust and POS) successfully mediate the sources of the organization (procedural justice). Implications for the theory and practice are discussed.